Errors That Must Be Avoided in The laboratory to Achieve Maximum Accuracy in The Medical Analysis - Mansour Tayeh Maslet Ashammari, Turky Saud Saad Altamimi , Khalil Awadh Khalil Alshammari , Fahad Mohammed Ibrahim Alateeq , Faris Zamel Saleh Alserheed, Turki Awadh Aqeel Alharbi (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Owing to increasing attention focused on patient safety and the need to decrease laboratory errors, it is necessary that clinical laboratories collect statistical data on error occurrence rates over the all testing cycle, involving pre-, intra-, and post-analytic phases. Methods: This descriptive aims to evaluate the frequency of errors before, during, and after analysis in a major medical laboratory. There for we can determine the factors causing these errors to avoid them, improve the work strategy in clinical laboratories so obtain highly accurate medical reports, it analyses data from observational studies, surveys, and intervention trials. Results: The results show that the most laboratory errors induced during pre-analytical stage, the good training and knowledge of the intervening factors that can influence laboratory results are necessary to reduce laboratory errors. It is recommended that the three phases of laboratory tests need to be under thorough monitoring so that improve the accuracy and the quality of results. Discussion: The findings of the literature review show that despite heterogeneity in methods, the errors may occur through the different stages of testing process. Despite the importance of pre-analytic stage has been known for many years, laboratories usually missed this point in their quality management program and focusing on the analytic quality and the activities associated within their direct control. We should know that it is unrealistic to decrease the laboratory testing errors totally especially those relating to extra-analytic stages which are difficult to control, The necessary of good laboratory practice and compliance with the new accreditation standards, that include good strategies to prevent the error as process redesign, the use of extra-analytic specifications and improve the communication between laboratory technicians. Finally, it is recommended that laboratories with high volume of work need to be equipped with HIS system. This will help the laboratory staff to be undercut and errors could be minimized.